Gender Differences in Reflective Practice of EFL Student Teachers in Microteaching - Suryani, Fitri Budi (Universitas Islam Nahdlatul Ulama Jepara, 2024)
Reflection is a crucial phase for student teachers in conducting their teaching practice in microteaching. It enables them to evaluate, critizise, and judge their teaching practice as well as seek improvement for their better teaching practice. Some research revealed the differences of reflection conducted by female and male educators and teachers. This qualitative study aims at exploring the female and male EFL student teachersâ€™ reflection of their teachng practice in microteaching regarding the level and the theme of reflection. The participants were thirty-four sixth semester students enrolling in microteaching course at English Education Department of Â a private university in Indonesia. Those EFL student teachers were required to write reflection journal after attending their peersâ€™ teaching practice. The teaching practices were recorded and shared to the students so that they could watch them again out of the classroom before writing their reflection. The result of the study indicates that the female and male EFL student teachers vary in their different level of reflection in microteaching. They also differ in the theme of reflection, in which the female EFL student teachers reflected more themes of teaching practice than their male peers.